Ergonomics and Human Factors for a Sustainable Future Current Research and Future Possibilities (Springer Singapore, 2018)
"This book is an interesting compilation of different perspectives on HFE in the sustainable development field. The book is multidisciplinary and multi-context, with authors drawing examples from developing and developed countries to provide balanced and inclusive solutions to sustainability challenges." - Professor Jörgen Eklund, KTH Royal Institute of Technology, Sweden "All of the current researchers publishing in this field are well-represented, as is an overarching vision of the human contribution to sustainability. The matters presented in this book are of utmost importance, not only to ergonomists but to the world at large." -Colin Drury, University at Buffalo, State University of New York, USA "By stretching the borders of the discipline and profession, the authors show how HFE's unique features of design-orientation, systems approach, and combining well-being and performance, can be utilized to facilitate sustainability. The book can inspire HFE researchers, teachers and practitioners to contextualize and expand their current work, and to contribute to a sustainable future." -Professor Jan Dul, Erasmus University, The Netherlands This book focuses on different sustainable products and services, such as electrical vehicles, green buildings, and biophilic and biomimetic systems, at multiple hierarchical levels within its chapters. The authors reflect on individual, organisational, governmental, political, and moral considerations of how Human Factor Ergonomics can build a sustainable future. This book is a must-read for anyone concerned with environmental issues and sustainability. Andrew Thatcher is Professor of Industrial and Organisational Psychology at the University of the Witwatersrand, Johannesburg. His research focuses on understanding sustainable work systems. He is Chair of the International Ergonomics Association's Technical Committee on 'Human Factors for Sustainable Development' and is one of the editors of the journal Ergonomics. Paul H.P. Yeow is Associate Professor and former Head of Marketing Discipline at the School of Business, Monash University Malaysia. Paul has completed 14 research funded projects related to human factors, sustainable production, information systems and marketing and published over 50 journal articles. He is a member of editorial board of Applied Ergonomics.